Meningkatkan Preservasi DNA asal Saliva melalui Inaktivasi DNase I: Peran Suhu dan EDTA - Yamamoto, Zulham; Sulviani, Nurul; Widjaja, Sry Suryani (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Deoxyribonuclease I (DNase I) catalyzes the cleavage of double-stranded DNA into its end products. This enzyme requires cations for its activity. In addition, DNase activity is influenced by indirect DNase inhibitors (i.e. EDTA) and temperature. EDTA is an indirect DNase I inhibitor. Therefore, DNase inactivation is crucial for DNA preservation, especially for salivary samples, and the downstream application of genetic techniques using non-blood samples. Saliva is a complex mixture contaminated with oral microbes and contains DNase which is harmful for DNA preservation. This study aims to preserve salivary DNA through temperature and EDTA treatment. Methods This is an experimental study. Salivary DNA was extracted using the spin-column method. DNA degradation assays were carried out using either 5 µL of salivary supernatant or 2.5 mg/mL of DNase I which were incubated at -20°C, 2-8°C, room temperature, 40°C, and 50°C; and added with 0.125 mM, 0.25 mM, 0.5 mM, 1 mM, and 2 mM EDTA for 60 minutes. After incubation, the results were visualized using agarose gel electrophoresis. Results The average concentration of salivary DNA was 61.70 µg/mL (30.50-109.05) and the purity was 1.893 µg/mL (1.800-2.005). Incubation at -20°C, 2-8°C, and room temperature degraded salivary DNA but incubation at 40 and 50°C did not completely degrade DNA. Addition 0.125 mM, 0.25 mM, 0.5 mM, 1 mM, and 2 mM EDTA to 5 µL of salivary supernatant or 2.5 mg/mL DNase I preserved salivary DNA. Conclusions Temperature of 40 and 50°C, and 0.125 mM EDTA can inactivate DNase and preserve salivary DNA.